Dissecting the Role of Critical Residues and Substrate Preference of a Fatty Acyl-CoA Synthetase (FadD13) of Mycobacterium tuberculosis - Khare, Garima (Public Library of Science, 2009)

(untitled)
Newly emerging multi-drug resistant strains of Mycobacterium tuberculosis (M.tb) severely limit the treatment options for tuberculosis (TB); hence, new antitubercular drugs are urgently needed. The mymA operon is essential for the virulence and intracellular survival of M.tb and thus represents an attractive target for the development of new antitubercular drugs. This study is focused on the structure-function relationship of Fatty Acyl-CoA Synthetase (FadD13, Rv3089) belonging to the mymA operon. Eight site-directed mutants of FadD13 were designed, constructed and analyzed for the structural-functional integrity of the enzyme. The study revealed that mutation of Lys(487) resulted in ∼95% loss of the activity thus demonstrating its crucial requirement for the enzymatic activity. Comparison of the kinetic parameters showed the residues Lys(172) and Ala(302) to be involved in the binding of ATP and Ser(404) in the binding of CoenzymeA. The influence of mutations of the residues Val(209) and Trp(377) emphasized their importance in maintaining the structural integrity of FadD13. Besides, we show a synergistic influence of fatty acid and ATP binding on the conformation and rigidity of FadD13. FadD13 represents the first Fatty Acyl-CoA Synthetase to display biphasic kinetics for fatty acids. FadD13 exhibits a distinct preference for C(26)/C(24) fatty acids, which in the light of earlier reported observations further substantiates the role of the mymA operon in remodeling the cell envelope of intracellular M.tb under acidic conditions. A three-dimensional model of FadD13 was generated; the docking of ATP to the active site verified its interaction with Lys(172), Ala(302) and Lys(487) and corresponded well with the results of the mutational studies. Our study provides a significant understanding of the FadD13 protein including the identification of residues important for its activity as well as in the maintenance of structural integrity. We believe that the findings of this study will provide valuable inputs in the development of inhibitors against the mymA operon, an important target for the development of antitubercular drugs.